Management of Postpartum Anestrus in Beef Cows - Kalyn Bischoff; Vitor Mercadante; G. Cliff Lamb (EDIS)
It is estimated that in Florida alone the cost of infertility of beef cows exceeds $86 million annually. Infertility occurs when cows become pregnant but fail to calve, become pregnant late in the breeding season and fall out of the annual production cycle or fail to become pregnant during the breeding season. The latter two causes of infertility are a direct result of the length of the post-partum interval. This 4-page fact sheet was written by Kalyn Bischoff, Vitor Mercadante, and G. Cliff Lamb, and published by the UF Department of Animal Science, March 2012.